Effectiveness, Safety, and Barriers to Early Mobilization in the Intensive Care Unit - Gopala Krishna Alaparthi; Aishwarya Gatty; Stephen Rajan Samuel; Sampath Kumar Amaravadi (Critical Care Research and Practice)
Purpose. Patients admitted to the intensive care unit (ICU) are generally confined to bed leading to limited mobility that may have detrimental effects on different body systems. Early mobilization prevents or reduces these effects and improves outcomes in patients following critical illness. The purpose of this review is to summarize different aspects of early mobilization in intensive care. Methods. Electronic databases of PubMed, Google Scholar, ScienceDirect, and Scopus were searched using a combination of keywords. Full-text articles meeting the inclusion criteria were selected. Results. Fifty-six studies on various aspects such as the effectiveness of early mobilization in various intensive care units, newer techniques in early mobilization, outcome measures for physical function in the intensive care unit, safety, and practice and barriers to early mobilization were included. Conclusion: Early mobilization is found to have positive effects on various outcomes in patients with or without mechanical ventilation. The newer techniques can be used to facilitate early mobilization. Scoring systems—specific to the ICU—are available and should be used to quantify patients’ status at different intervals of time. Early mobilization is not commonly practiced in many countries. Various barriers to early mobilization have been identified, and different strategies can be used to overcome them.